Analisis Persepsi Mahasiswa PAI Terhadap Efektivitas Program PLP Dalam Pengembangan Kompetensi Keprofesian Guru: Studi Kasus Di Universitas Qomaruddin - Moh. Hasan Amin; M. Nawawi (JURNAL MANAJEMEN PENDIDIKAN, 2026)
ANALYSIS OF PAI STUDENTS' PERCEPTION TOWARDS THE EFFECTIVENESS OF THE PLP PROGRAM IN DEVELOPING TEACHER PROFESSIONAL COMPETENCIES: A CASE STUDY AT QOMARUDDIN UNIVERSITY This study aims to critically analyze the perceptions of Islamic Education (PAI) students at Universitas Qomaruddin regarding the effectiveness of the Field Introduction Program (PLP) in developing professional teaching competencies. The study is based on the persistent gap between theoretical pedagogical knowledge acquired in higher education and the realities of classroom practice, which affects the professional readiness of prospective teachers. This research employs a qualitative approach using a case study design. Data were collected through semi-structured interviews and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings indicate that the PLP program has not yet functioned optimally in developing professional competencies. Students tend to perceive PLP as an introductory field experience with limited teaching practice opportunities. In addition, there is a gap between academic preparation and real school conditions, uneven mentoring quality, and limited meaningful pedagogical practice space. As a result, PLP is more dominant in observational functions rather than strengthening professional competencies.